2006
DOI: 10.1080/10893950600643014
|View full text |Cite
|
Sign up to set email alerts
|

Size Effects of Miniature Refrigeration and Liquefaction System

Abstract: This article examines the size effects on the performance of miniature refrigerators and liquefiers operated by the Linde cycle. The system sizes are cased into a function of the compressor characteristic length and the heat exchanger length while several cycle operation parameters are held constant. Simplified models of a Hampson-type counterflow heat exchanger and a reciprocating-type compressor were considered in the present analysis.For both the refrigerator and the liquefier, it was found that only for ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Greek Letters ε coefficient of performance λ thermal wavelength, m μ chemical potential, J liquefaction system [9] was discussed. It has been shown that the finite-size effect is of the order of λ/L * , which is negligible for classical gases but may be significant for degenerate quantum gas systems [6], where L * is the representative linear dimension of the container, λ = h/ √ 2π mk B T is the thermal wavelength of particles at temperature T, h is Planck's constant, k B is Boltzmann's constant, and m is the mass of a particle.…”
Section: Nomenclaturementioning
confidence: 99%
“…Greek Letters ε coefficient of performance λ thermal wavelength, m μ chemical potential, J liquefaction system [9] was discussed. It has been shown that the finite-size effect is of the order of λ/L * , which is negligible for classical gases but may be significant for degenerate quantum gas systems [6], where L * is the representative linear dimension of the container, λ = h/ √ 2π mk B T is the thermal wavelength of particles at temperature T, h is Planck's constant, k B is Boltzmann's constant, and m is the mass of a particle.…”
Section: Nomenclaturementioning
confidence: 99%